Length of occlusion predicts recanalization and outcome after intravenous thrombolysis in middle cerebral artery stroke - Rohan, Vladimir; Baxa, Jan; Tupy, Radek; Cerna, Lenka; Sevcik, Petr; Friesl, Michal; Polivka, Jiri; Polivka, Jiri; Ferda, Jiri (Stroke, 2014)
BACKGROUND AND PURPOSE: The length of large vessel occlusion is considered a major factor for therapy in patients with ischemic stroke. We used 4D-CT angiography evaluation of middle cerebral artery occlusion in prediction of recanalization and favorable clinical outcome and after intravenous thrombolysis (IV-tPA). METHODS: In 80 patients treated with IV-tPA for acute complete middle cerebral artery/M1 occlusion determined using CT angiography and temporal maximum intensity projection, calculated from 4D-CT angiography, the length of middle cerebral artery proximal stump, occlusion in M1 or M1 and M2 segment were measured. Univariate and multivariate analyses were performed to define independent predictors of successful recanalization after 24 hours and favorable outcome after 3 months. RESULTS: The length of occlusion was measureable in all patients using temporal maximum intensity projection. Recanalization thrombolysis in myocardial infarction 2 to 3 was achieved in 37 individuals (46%). The extension to M2 segment as a category (odds ratio, 4.58; 95% confidence interval, 1.39-15.05; P=0.012) and the length of M1 segment occlusion (odds ratio, 0.82; 95% confidence interval, 0.73-0.92; P=0.0007) with an optimal cutoff value of 12 mm (sensitivity 0.67; specificity 0.71) were significant independent predictors of recanalization. Favorable outcome (modified Rankin scale 0-2) was achieved in 25 patients (31%), baseline National Institutes of Health Stroke Scale (odds ratio, 0.82; 95% confidence interval, 0.72-0.93; P=0.003) and the length of occlusion M1 in segment (odds ratio, 0.79; 95% confidence interval, 0.69-0.91; P=0.0008) with an optimal cutoff value of 11 mm (sensitivity 0.74; specificity 0.76) were significant independent predictors of favorable outcome. CONCLUSIONS: The length of middle cerebral artery occlusion is an independent predictor of successful IV-tPA treatment.
Keywords: Humans; čtyřrozměrná počítačová tomografie; lidé středního věku; Predictive Value of Tests; Thrombolytic Therapy; trombolytická terapie; Aged; Female; dospělí; middle cerebral artery; výsledek terapie; senioři; lidé; Tissue Plasminogen Activator; Cerebral Angiography; stroke; outcome; thrombolytic therapy; fibrinolytika; Adult; mozková angiografie; Fibrinolytic Agents; ženské pohlaví; Male; tkáňový aktivátor plazminogenu; prediktivní hodnota testů; Middle Aged; Retrospective Studies; infarkt arteria cerebri media; Treatment Outcome; Cerebrovascular Circulation; Infarction, Middle Cerebral Artery; Aged, 80 and over; senioři nad 80 let; mozkový krevní oběh; retrospektivní studie; computed tomography; Four-Dimensional Computed Tomography; mužské pohlaví